The influence of trust, corporate image on customer satisfaction and customer loyalty (study on J&T express bangetayu customers, Semarang) - Wibowo, Angella Nurul Chanitta; Bambang Sutedjo; Sri Sumiyati (SEAN Institute, 2024)
The aim of this research is to analyze the influence of trust, corporate image on customer satisfaction and customer loyalty of J&T Express Bangetayu, Semarang customers. This study is classified as quantitative. This study has a population of people from J&T Express Bangetayu, Semarang, with a sample size of 102 respondents. How to determine the sample using purposive sampling. The analytical tool used is the SPSS version 26 statistics program which can determine the relationship between variables using multiple linear regression analysis. The results can be summarized as: confidence has a good effect on people's feelings of satisfaction. The company's image has a good effect on people's satisfaction. People's satisfaction has a good effect on people's loyalty